Management of Copper Deficiency in Cholestatic Infants: Review of the Literature and a Case Series. (15th October 2012) - Blackmer, Allison Beck; Bailey, Elizabeth
Abstract : Copper is an essential trace element, playing a critical role in multiple functions in the body. Despite the necessity of adequate copper provision and data supporting the safety of copper administration during cholestasis, it remains common practice to reduce or remove copper in parenteral nutrition (PN) solutions after the development of cholestasis due to historical recommendations supporting this practice. In neonates, specifically premature infants, less is known about required copper intakes to accumulate copper stores and meet increased demands during rapid growth. Pediatric surgical patients are at high risk for hepatic injury during long‐term PN provision and a balance is needed between the potential for reduced biliary excretion of copper and adequate copper intakes to prevent deficiency. Copper deficiency has been documented in several pediatric patients with cholestasis when parenteral copper was reduced or removed. Few data guide the management of copper deficiency in the pediatric population. The following case series describes our experience with successfully managing copper deficiency in 3 cholestatic infants after copper had been reduced or removed from their PN. Classic signs of copper deficiency were present, including hypocupremia, anemia, neutropenia, thrombocytopenia, and osteopenia. Treatment included use of both parenteral and enteral copper supplementation. We suggest revision of current recommendations regarding decreasing copper in PN during cholestasis with a proposed algorithm for parenteral copper provision in the setting of cholestasis that is based on evaluation of measured serum copper concentrations.